Особливості застосування гідрокінезотерапії та дієтотерапії в комплексному лікуванні дівчат-підлітків з аліментарною формою ожиріння - Андрійчук, Ольга Ярославівна; Andriіchuk, Olga Ya. (Національний педагогічний університет імені М. П. Драгоманова, 2015)
У статті представлений огляд літературних даних, в яких обґрунтовано необхідність застосування гідрокінезотерапії і дієтотерапії у підлітків з аліментарної формою ожиріння. Автором пояснюється перевага застосування методики занять у воді в порівнянні з іншими засобами і методами комплексної терапії, які використовуються в лікуванні пацієнтів, які страждають ожирінням. На підставі результатів інструментальних методів дослідження 48 дівчат з екзогенно-конституціональним ожирінням у віці 12-16 років виявлена переважна ефективність запропонованої програми фізичної реабілітації по відношенню до стандартної методики. The review of literary data in that the necessity of application of hidrokinezeterapii and dietotherapy is reasonable for teenagers with the alimentary form of obesity is presented in the article. An author is explain advantage of application of methodology of employments in water as compared to other facilities and methods of complex therapy, that is used in treatment of patients suffering obesity. The estimation of efficiency of an offer program of the physical rehabilitation, based on the results of supervision 48 girls with exogenous-constitutional obesity in age 12-16, taking treatment on the base of laboratories of NUFKS and National center of radiation medicine of АМS of Ukraine, is presented. First - basic group (ОГ), (n = 20) made persons with obesity 1-2 degrees, that occupied on the worked out methodology (dietotherapy and hidrokinezeterapia). Second - control group (KG),(n = 28) girls made with obesity 1-2 degrees, that occupied on methodology of curative establishment(dietotherapy and curative gymnastics). The course of treatment lasted 4 months. As a result, from data of the controlled from distance method of measuring of composition of body of BC - 418MA TANITA and standard laboratory analyses of blood, that consisted of biochemical blood test, the high level of effectiveness of original methodology of rehabilitation is educed as compared to the standard methods of treatment, that allows to recommend her introduction in rehabilitation centers and sanatory establishments for treatment of children and teenagers with the presented pathology.
Features of application of hidrokinezeterapii and dietotherapy are in the holiatry of girls - teenagers with the alimentary form of obesity
Keywords: ожиріння; гідрокінезотерапія; компонентний склад тіла; obesity; hidrokinezeterapii; component composition of body